WhatsApp groups: channel for sharing information among LIS professionals in Nigeria. Issue 4 (8th September 2020) - Udem, Obiora Kingsley; Aghoghovwia, Doris U.; Baro, Ebikabowei Emmanuel
Abstract : Purpose: The purpose of this study is to determine the type of information Library and Information Science professionals share in the WhatsApp groups in Nigeria. Design/methodology/approach: The study adopted a quantitative content analysis research design. With a total of 739 participants, 1, 385 posts of six different WhatsApp groups of Library and Information Science professionals for three months were analyzed. Findings: The study found that the most shared information among the Library and Information Science professionals in Nigeria is post on professional information. This demonstrates that librarians are determined to share professional information among them to promote the profession. This was followed by political information basically on the Nigerian Library Association national executives' election, and job advertisements related to the library. Although a few members violate the rules by posting the kind of information not required in the WhatsApp group, the erring members are quickly called to order and warned by the WhatsApp group administrator. Social implications: Professional ties can grow among information specialists and library practitioners through participation in virtual communities such as WhatsApp group. The implication of this work is in showing that social media especially WhatsApp groups can be used as a knowledge sharing mechanism to share timely, current and relevant information among professionals in different occupations. Originality/value: Findings on the use of WhatsApp group in sharing professional information will inform several other Library and Information Science professionals in other countries of the need to adopt this channel to disseminate timely information related to up-coming conferences, training opportunities, workshops, call for papers and so on among the professionals. The results of this paper are valuable for anyone interested in an avenue to share or receive much quicker and pertinent information that saves the time of professionals in any occupation.